Effect of Profitability, Liquidity and Leverage on Tax Aggressiveness - Petrina Gloria Christy (Journal of World Conference (JWC), 2023)
This study aims to examine and obtain empirical evidence of the effect of profitability, liquidity and leverage on tax aggressiveness. Sampling using purposive sampling method obtained a sample of 19 companies with 76 data. The population in this study are manufacturing companies in the consumer goods industry sector which are listed on the Indonesia Stock Exchange during the period 2017-2020. The regression model in this study is multiple linear regression analysis. The results showed that profitability had a negative and significant effect on tax aggressiveness. Liquidity has a positive and significant effect on tax aggressiveness. Leverage has a positive and significant effect on tax aggressiveness.